Classical Guidance Through Habituation of Listening Speaking Reading and Writing to Improve Arabic Language Skills in Syarifudin Students - Irsyada, Mahmud (Risalatuna Journal of Pesantren Studies, 2025)
This article examines the pivotal role of the Arabic language program at Kyai Syarifuddin pesantren in enhancing students’ linguistic competencies. The program employs a classical guidance approach through the habituation of four fundamental language skills: listening, speaking, reading, and writing. These structured practices serve as an effective method for deepening students’ understanding and application of Arabic. The program involves all students in the pesantren, providing them with opportunities to internalize the learning process, recognize their potential, and overcome linguistic challenges. This study investigates two main research questions: (1) How is classical guidance implemented in Arabic language instruction? and (2) What are the outcomes of this implementation?. The study adopts a qualitative case study methodology. Data were collected through participatory observation, in-depth interviews with the Arabic program coordinator, instructors, and participating students, as well as document analysis related to students’ Arabic proficiency. The data analysis was grounded in classical guidance theory. The findings reveal two key conclusions: (1) the implementation of classical guidance in Arabic instruction is carried out through consistent habituation of listening, speaking, reading, and writing skills; and (2) this approach results in learning outcomes that are effective, efficient, and meaningful for students’ overall language development.